Artificial spider silk from ion-doped and twisted core-sheath hydrogel fibres - Yuanyuan Dou (Nature Portfolio, 2019)
Different models are believed to be the reason for the superior mechanical properties of spider silk. Here, the authors prepare artificial spider silk by water-evaporation-induced self-assembly of a hydrogel fibre made from polyacrylic acid and silica nanoparticles.